Human Security and Japanese Foreign Policy: Context, Concept and Application - Caterina Garcia Segura (Revista CIDOB d'Afers Internacionals, 2007)
Japan has assumed the concept of human security as a key aspect in its foreign policy, and this country has become one of its great promoters at an international level. This acceptance has been accompanied by an option: while Japan admits the dual aspect of theconcept (freedom from fear and freedom from want), it has been leaning toward the aspects that link human security and freedom from situations of extreme deprivation and which make reference to the structural causes that link security and development. This articleanalyses the evolution of the Japanese conception of human security and its practical application, bearing in mind the context in which it is shaped and developed. It defends the thesis that it is an instrument that responds to the Japanese government’s need to provide a response to internal and external pressures for renovation of a reactive, low-profile foreign policy, without altering those elements whose reform could cause negative reactions in the countries of East Asia and a good part of its public opinion.